We Dive at Dawn - Asquith, Anthony; Cox, Jack; Mills, John; Bradfield, Louis; Millar, Ronald (John Mills Centenary Collection I)
During the war, the Sea Tiger, a British submarine with Lt. Taylor as captain, docks at a naval port. Seven days leave is given, various members of the crew go home to their families. Shortly afterwards they are all recalled to the submarine. They are given secret orders to pursue and sink the Nazi battleship Brandenburg. After sinking a German wireless buoy and taking prisoners in the North Sea, the submarine sights the battleship and fires its torpedoes. Conditions prevent the crew knowing whether they have succeeded in their mission. They evade German destroyers by playing ‘dead’, but run out of fuel off the Danish coast. Leading Seaman Hobson, who can speak German, goes ashore in one of the German prisoners’ uniforms and reconnoitres. He discovers a Danish tanker in the dock and signals the Sea Tiger to proceed into the shore. The Nazis discover the submarine while it is refuelling but with the aid of friendly Danish patriots the Sea Tiger manages to refuel and submerge, finally arriving back to safety at an English port. [www.britmovie.co.uk]